Diabetic retinal neurodegeneration as a form of diabetic retinopathy - Soni, Deepak; Sagar, Pradeep; Takkar, Brijesh (International ophthalmology, 2021)
Purpose To review the evidence supporting diabetic retinal neurodegeneration (DRN) as a form of diabetic retinopathy. Method Review of literature. Results DRN is recognized to be a part of retinopathy in patients with diabetes mellitus (DM), in addition to the well-established diabetic retinal vasculopathy (DRV). DRN has been noted in the early stages of DM, before the onset of clinically evident diabetic retinopathy. The occurrence of DRN has been confirmed in animal models of DM, histopathological examination of donor’s eyes from diabetic individuals and assessment of neural structure and function in humans. DRN involves alterations in retinal ganglion cells, photoreceptors, amacrine cells and bipolar cells, and is thought to be driven by glutamate, oxidative stress and dysregulation of neuroprotective factors in the retina. Potential therapeutic options for DRN are under evaluation. Conclusions Literature is divided on the temporal relation between DRN and DRV, with evidence of both precedence and simultaneous occurrence. The relationship between DRN and multi-system neuropathy in DM is yet to be evaluated critically.